2002
DOI: 10.1074/jbc.m204733200
|View full text |Cite
|
Sign up to set email alerts
|

Hsp90 Regulates a von Hippel Lindau-independent Hypoxia-inducible Factor-1α-degradative Pathway

Abstract: HIF-1␣ is a normally labile proangiogenic transcription factor that is stabilized and activated in hypoxia. Although the von Hippel Lindau (VHL) gene product, the ubiquitin ligase responsible for regulating HIF-1␣ protein levels, efficiently targets HIF-1␣ for rapid proteasome-dependent degradation under normoxia, HIF-1␣ is resistant to the destabilizing effects of VHL under hypoxia. HIF-1␣ also associates with the molecular chaperone Hsp90. To examine the role of Hsp90 in HIF-1␣ function, we used renal carcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
464
0
10

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 634 publications
(495 citation statements)
references
References 66 publications
21
464
0
10
Order By: Relevance
“…Adding GA to 6 h hypoxic treated prostate cells resulted in a decrease in HIF-1a protein levels in all the four cell lines. Isaacs et al 20 showed that the addition of GA promotes the degradation of HIF-1a under hypoxia rather than preventing HIF-1a upregulation. Our results show that neither hypoxia nor GA have any effect on HIF-1a mRNA levels.…”
Section: Inhibition Of Hif-1a By Geldanamycinmentioning
confidence: 99%
See 1 more Smart Citation
“…Adding GA to 6 h hypoxic treated prostate cells resulted in a decrease in HIF-1a protein levels in all the four cell lines. Isaacs et al 20 showed that the addition of GA promotes the degradation of HIF-1a under hypoxia rather than preventing HIF-1a upregulation. Our results show that neither hypoxia nor GA have any effect on HIF-1a mRNA levels.…”
Section: Inhibition Of Hif-1a By Geldanamycinmentioning
confidence: 99%
“…Hsp90 also cooperates with the proteasomal pathway to eliminate misfolded cellular proteins. 20,21 The antibiotic GA associates with Hsp90 and modulates its chaperone function by accelerating the degradative activity associated with Hsp90. 22,23 The ability of GA to promote the proteasome-dependent degradation of client proteins including HIF-1a provides it as a potential antitumor agent.…”
Section: Introductionmentioning
confidence: 99%
“…The requirement of pVHL for HIF-1␣ degradation is underscored in cells that do not contain a functional pVHL, which leads to high levels of HIF-1␣ in normoxia (Maxwell et al, 1999;Krieg et al, 2000;Clifford et al, 2001). However, recently, a pVHL-and oxygen-independent HIF-1␣ degradation pathway has been reported (Isaacs et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The requirement of pVHL for HIF-1␣ degradation is underscored in cells that do not contain a functional pVHL, which leads to high levels of HIF-1␣ in normoxia (Maxwell et al, 1999;Krieg et al, 2000;Clifford et al, 2001). However, recently, a pVHL-and oxygen-independent HIF-1␣ degradation pathway has been reported (Isaacs et al, 2002).In normoxia HIF-1␣ is hydroxylated at Pro564 and Pro402, which is required for pVHL binding Jaakkola et al, 2001;Masson et al, 2001;Yu et al, 2001). Prolyl hydroxylation is performed by enzymes sharing homology with the EGL-9 protein from Caenorhabditis elegans (Epstein et al, 2001).…”
mentioning
confidence: 99%
“…Further experiments are needed to resolve why some cell lines arrest in G 1 -phase, whereas others do so in G 2 /M. Similarly, some studies report a degradation of HIF1a after Hsp90 inhibition (40), whereas others show merely a delayed accumulation of the protein (25) or an inhibition of the transcriptional activity (41). These differences may be explained by the individual study conditions and biological systems used.…”
Section: Discussionmentioning
confidence: 99%